Lethal femoral-facial syndrome: a case with unusual manifestations. Issue 6 (June 1997) - Gillerot, Y; Fourneau, C; Willems, T; Van Maldergem, L
Abstract : The femoral-facial syndrome is a very rare syndrome of uncertain inheritance comprising hypoplastic femora, microretrognathia, and a peculiar facies. We report an additional observation detected by ultrasound at 25 weeks and diagnosed at birth. In addition to the malformations usually described in this syndrome, there were heterotopias of the brain, partial agenesis of the corpus callosum, bilobed lungs, intestinal malrotation, and vertebral segmentation defects.